Optimizing Teacher Questioning Strategies for Enhanced Reading Comprehension in EFL Classrooms - Masduki (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: Recent developments in reading theory emphasize the significance of an interactive approach to reading comprehension in EFL contexts. This study investigates the role of teacher questioning strategies in promoting effective reading comprehension in EFL classrooms. Methodology: This qualitative classroom research studied teacher questioning and students' responses in reading comprehension classes using non-participant observation and interviews to assess the effectiveness of EFL teacher questioning. Findings: EFL teachers in reading classes used closed and open forms of display and referential questions. They employed questioning strategies such as translation, repetition, and pausing. Modifications included probing and rephrasing to improve students' engagement and comprehension. Conclusion: In conclusion, the study found that EFL teachers in reading comprehension courses used a range of effective questioning techniques, including translation, repetition, pausing, probing, and rephrasing, to enhance student engagement and comprehension. However, the use of complex or punishing questions can impede effective questioning. Originality: The novelty of this study lies in investigating the types of questions and strategies employed by EFL teachers in reading comprehension courses. Additionally, the study provides insight into the relationships among the different types of questions and strategies, and their effects on student engagement and comprehension.